PENGEMBANGAN MEDIA PEMBELAJARAN MOBILE LEARNING BERBASIS ANDROID DENGAN ISPRING SUITE PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK KELAS XI JURUSAN TEKNIK INSTALASI TENAGA LISTRIK DI SMK SWASTA IMELDA MEDAN - Rico Faul Yohannes Sinaga; Nelson Sinaga (Universitas Negeri Medan, 2021)
Abstract Development of Android-based Mobile Learning Media with Ispring Suite in Electrical Motor Installation Subjects Class XI Department of Electrical Installation Engineering at Imelda Private Vocational School Medan, 2020. This study aims to find out the design of a media Development of Android-based Mobile Learning Media with Ispring Suite in Electrical Motor Installation Subjects Class XI Department of Electrical Installation Engineering at Imelda Private Vocational School Medan and test the feasibility of Android-based Mobile Learning learning media designed as a learning medium for students. This research was conducted on grade XI students of TITL SMK Swasta Imelda Medan in the 2019/2020 school year. This research was tested to lecturers and teachers. The procedure of developing Android-based learning media in the subjects of installing a simple building electric motor installation packaged in the form of interactive softcopy/CD software is carried out using the R&D method of ADDIE development design. As well as the media feasibility validation processAbstract must reflect the overall substance of the article content and be able to help readers determine its relevance to their interests and decide whether to read the document in its entirety, esearchers use the ADDlE method in research and development. The results of this study showed the validation of the poll of media experts with an average of 4.20 interpretations is very good and very worthy to be used as a medium of learning. Validation of material experts (content experts) with an average of 4.72 interpretations is very well used as a medium of learning. User validation with an average of 4.16 interpretations is very good and very worthy to be used as a learning medium. Key Words: Development, Learning Media, Electrical Motor Installation AbstrakPengembangan Media Pembelajaran Mobile Learning Berbasis Android dengan Ispring Suite pada Mata Pelajaran Instalasi Motor Listrik Kelas XI Jurusan Teknik Instalasi Tenaga Listrik di SMK Swasta Imelda Medan, 2020. Penelitian ini bertujuan untuk mengetahui rancangan sebuah media Pengembangan Media Pembelajaran Mobile Learning Berbasis Android dengan Ispring Suite pada Mata Pelajaran Instalasi Motor Listrik Kelas XI Jurusan Teknik Instalasi Tenaga Listrik di SMK Swasta Imelda Medan dan menguji kelayakan media pembelajaran Mobile Learning berbasis Android yang dirancang sebagai media pembelajaran bagi siswa. Penelitian ini dilakukan pada siswa kelas XI TITL SMK Swasta Imelda Medan tahun ajaran 2019/2020. Penelitian ini diuji cobakan kepada Dosen dan Guru. Prosedur pengembangan media pembelajaran berbasis Android pada mata pelajaran memasang instalasi motor listrik bangunan sederhana yang dikemas dalam bentuk software softcopy/CD interaktif dilakukan dengan menggunakan metode R&D desain pengembangan ADDIE. Serta proses validasi kelayakan media, peneliti menggunakan metode ADDlE dalam penelitian dan pengembangan (Research and Development). Hasil penelitian ini menunjukkan validasi angket ahli media dengan rata-rata 4,20 interpretasi sangat baik dan sangat layak digunakan sebagai media pemebelajaran. Validasi ahli materi (pakar konten) dengan rata-rata 4,72 interpretasi sangat baik digunakan sebagai media pembelajaran. Validasi user dengan rata-rata 4,16 interpretasi sangat baik dan sangat layak digunakan sebagai media pembelajaran. Kata Kunci: : Pengembangan, Media Pembelajaran, Instalasi Motor Listrik